Juridical Analysis of Corruption Crime Asset Confistion As an Effort to Return State Losses Using Non Penal Approach in Indonesia - Fauzan Akbar; Khaerul Ardhian Syaekh (Asian Journal of Social and Humanities, 2023)
In its development, corruption in Indonesia has increased from year to year, both in terms of the quality or amount of state financial losses and the quality of how it is carried out in a sophisticated and systematic manner, and has even penetrated across national borders. Therefore, handling corruption, especially in order to maximize the recovery of state losses, requires a comprehensive approach, as well as through international cooperation. This research found the fact that the asset confiscation mechanism using a non-penal approach is more effective and efficient. This argument is based on the fact that because there is no need to confirm the crime of corruption as long as the perpetrator's assets are suspected to be illegal assets of corruption, this shortens the time. Confiscation of property or assets using non-penal means is more efficient when compared to confiscation of property or assets through civil means in accordance with the provisions of the Corruption Eradication Law (PTPK) which is legal in Indonesia. Because if in a criminal case using civil law it is the same as placing the burden on the prosecutor to carry out proof, then it actually increases the number of things that might happen, namely reconvention lawsuits against the prosecutor as the plaintiff. The asset confiscation mechanism using a non-penal approach no longer focuses on chasing perpetrators but rather following the movement of money so that the number of corruption in Indonesia is expected to decrease.